Psychosocial Correlates of Psychological Distress among First Time Pregnant Mothers - Farwa Rasheed; Urooj Sadiq (Journal of Basic & Applied Sciences, 2017)
: Objective: The study investigated the relation of marital relationship and social support with psychological distress in first time pregnant women. Study Design: Correlational design. Setting and Duration: The study was carried out in Lahore, Pakistan, over a period of six months. Subjects and Methods: The sample of the present study includes 100 pregnant first time mothers. Sample of pregnant females was collected from the maternity ward of different hospital located in Lahore. Pregnant females included in sample were falling with the age range of 20-35 years, the minimum duration of their marriage was at least 2 years and minimum qualification was intermediate. Those women were selected who had no history of psychological problem and had never been on any kind of psychiatric/ psychological treatment (psychotropic medication /psychotherapy). The participants completed the Demographic Information sheet, Depression Anxiety and Stress Scale, Relationship assessment Scale and Social Provision Scale. Responses were scored according to the producer given in the manuals. Results: Mean ± SD of age was 26.21 ± 2.8 years. Significant (p<.05) relationship was found between marital relationship and psychological distress among first time mothers whereas social support was also significant predictor of psychological distress among first time mothers. Conclusion: It is to be concluded that quality of marital relationship and social support affects on psychological distress of first time pregnant women.